Legislative Authority and Equal Partnership: A Juridical Analysis of the Role of Regional Houses of Representatives in Regional Regulation Making - Nirwan, Nirwan; Fahmal, A. Muin; Arif, Mohammad (CV. Social Politic Genius (SIGn), 2025)
Although designed as equal partners, the relationship between the Regional House of Representatives and the regional head in the legislative function often lacks synergy, yielding problematic legal outcomes. This study aims to systematically analyze the legislative authority of the Regional House of Representatives throughout the entire cycle of Regional regulation-making. Additionally, this study examines the essential standing of the Regional House of Representatives in its relationship with the regional head. Employing a normative legal research method through the statute approach and the conceptual approach, this study analyzes relevant primary and secondary legal materials. The results indicate that the legislative authority of the Regional House of Representatives is comprehensively manifested in every stage of Regional Regulation-making. These stages begin with planning within the regional legislation program, extend to the formulation of the Academic Paper, joint deliberations, and conclude with enactment and promulgation, placing it as a non-subordinate authority holder. Furthermore, it is concluded that the standing of the Regional House of Representatives relative to the regional head is fundamentally that of an equal partnership. This stance is grounded in the principles of decentralization and balanced political legitimacy. This equal standing is concretely manifested through the execution of the tri-functional role of the Regional House of Representatives (legislative, budgetary, and oversight), which is supported by an effective mechanism of checks and balances. This article presents a juridical analysis framework for examining the critical points within the regional legislative cycle, providing a reference for institutional reform.